2008
DOI: 10.1007/s00787-007-0622-3
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal mental representations about the child and mother–infant interaction at three months post partum

Abstract: Antenatal maternal representations about the child predicted parental regulatory ability and infant interaction behavior especially during the still-face period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 29 publications
0
11
0
2
Order By: Relevance
“…There is evidence that more positive or balanced prenatal representations of one's own mother (Ward & Carlson, 1995), the child‐to‐be (Dayton, Levondosky, Davidson, & Bogat, 2010; Flykt et al, 2009; Pearce & Ayers, 2005; Thun‐Hohenstein, Wienerroither, Schreuer, Seim, & Wienerroither, 2008), the self‐as‐mother, and the child's father (Coleman, Nelson, & Sundre, 1999) are important predictors of a more positive mother–infant relationship. The previous studies have not included the representations of the self‐as‐woman, and it thus is not possible to judge whether it would be a less salient predictor of mother–infant interaction quality than would other representational dimensions.…”
Section: Role Of Maternal Representationsmentioning
confidence: 99%
“…There is evidence that more positive or balanced prenatal representations of one's own mother (Ward & Carlson, 1995), the child‐to‐be (Dayton, Levondosky, Davidson, & Bogat, 2010; Flykt et al, 2009; Pearce & Ayers, 2005; Thun‐Hohenstein, Wienerroither, Schreuer, Seim, & Wienerroither, 2008), the self‐as‐mother, and the child's father (Coleman, Nelson, & Sundre, 1999) are important predictors of a more positive mother–infant relationship. The previous studies have not included the representations of the self‐as‐woman, and it thus is not possible to judge whether it would be a less salient predictor of mother–infant interaction quality than would other representational dimensions.…”
Section: Role Of Maternal Representationsmentioning
confidence: 99%
“…Women studies have shown that mother's mental representation of the infant as wells as mother-foetal attachment during pregnancy predicts postnatal maternal responses (Shin et al 2006;Siddiqui and Hagglof 2000;Thun-Hohenstein et al 2008). Therefore, in the current study, we investigated the impact of factors during pregnancy on responses to infant distress.…”
Section: Introductionmentioning
confidence: 96%
“…Although the sensitivity construct is successfully put in practice in this assessment, it can obviously be improved or new measuring alternatives can be experimented to better detect qualitative differences in the appropriateness of maternal responses to infant behavior. Finally, other predictive variables that were not investigated in this study probably play a role in understanding sensitivity and could help to explain the variance in that factor, such as maternal personality (Prinzie et al, 2009), social support and the relation with the infant's father , as well as infant-related variables (Mills-Koonce et al, 2007;Thun-Hohenstein et al, 2008).…”
Section: Final Considerationsmentioning
confidence: 97%
“…To give an example, Thun-Hohenstein, Wienerroither, Schreuer, Seim and Wienerroither (2008) assessed the affective bond between mother and fetus, using a questionnaire about maternal representations regarding the infant. In addition, in the third month of life, the interaction between mother and infant was recorded.…”
mentioning
confidence: 99%
See 1 more Smart Citation